A Qualitative Inquiry of K–12 Teachers’ Experience with Open Educational Practices: Perceived Benefits and Barriers of Implementing Open Educational Resources - Tang, Hengtao (International Review of Research in Open and Distributed Learning, 2020)
Teachers in K–12 schools have shown an increasing desire for open educational resources (OER) to ensure all students can learn effectively. OER provide teachers with free access to open-licensed educational resources that they can retain, reuse, revise, remix, and redistribute for personalized instruction. Open educational practices (OEP) have been considered a pathway to reinforce the acceptance and readiness of K–12 teachers to use OER. This research thus showcases a qualitative study that investigates teachers’ experiences with OEP. This research explains K-12 teachers’ perceived benefits of implementing OER and also discusses their perceived barriers hindering OER usage in K–12 settings. The study also discusses the practical implications of integrating OER in K–12 curriculum.